A high water-resistant gypsum-based cementitious material and a method of making the same

CN118324481BActive Publication Date: 2026-10-16HENAN POLYTECHNIC UNIV +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410289976.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-14
Publication Date
2026-10-16
Estimated Expiration
2044-03-14

AI Technical Summary

Technical Problem

[0008]本发明的目的在于提供一种高耐水性石膏基胶凝材料,兼顾耐水性好以及强度高的优势,以解决氟石膏大量堆积、利用不足、强度低、水硬性差以及适用环境受限的问题

Benefits of technology

[0026](1) This invention uses fluorogypsum as raw material, supplemented with fly ash, slag powder and a small amount of cement, and adds modified silica with hydrophilic and hydrophobic groups. The hydrophilic groups of the modified silica can ensure the normal hydration process, and the hydrophobic groups can prevent excessive water from penetrating the concrete, maintain the strength development of the concrete prepared by the fluorogypsum-based cementitious material, solve the problem of the fluorogypsum-based material being not water-resistant, and enable the fluorogypsum-based cementitious material to be used extensively in high humidity environments; in addition, the added CSH seed crystals can improve the early strength and are conducive to the formation of CSH.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118324481B_ABST
    Figure CN118324481B_ABST
Patent Text Reader

Abstract

The application provides a high-water-resistance gypsum-based cementing material and a preparation method thereof, and relates to the technical field of cementing materials.The high-water-resistance gypsum-based cementing material comprises the following raw materials in terms of mass ratio: fluorite gypsum 60-70%, fly ash 15-25%, cement 9-15%, slag powder 3-6%, modified silicon oxide 0.04-0.1%, and CSH crystal seed 0.1-0.5%, and further comprises a pH regulator and an activator; wherein the pH regulator accounts for 1-5% of the total mass of the fluorite gypsum and the fly ash, and the activator accounts for 0.5-3% of the total mass of the fluorite gypsum and the fly ash.The fluorite gypsum is used as the raw material, the fly ash, the slag powder and a small amount of cement are supplemented, and the modified silicon oxide with hydrophilic groups and hydrophobic groups is added, so that the problem of poor water resistance of the fluorite gypsum-based material is solved, and the fluorite gypsum-based cementing material can be used in a high-humidity environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of cementitious materials technology, specifically relating to a highly water-resistant gypsum-based cementitious material and its preparation method. Background Technology

[0002] Fluorogypsum is a waste residue from fluoride salt plants after producing hydrofluoric acid from fluorite and concentrated sulfuric acid. Its main chemical composition is anhydrous calcium sulfate (type II), containing a certain amount of residual calcium fluoride, sulfuric acid, hydrofluoric acid, a small amount of silicon dioxide, and trace amounts of sodium. + K + Impurities such as hydrofluoric acid are present. Theoretically, the production of 1 ton of hydrofluoric acid will generate 3.6 tons of fluorogypsum. Long-term stockpiling of fluorogypsum occupies a large amount of land resources, and the acidic leachate may pollute the surrounding ecological environment.

[0003] For some filling and solidification subgrade projects, the demand for filling materials mainly comes from cement. Cement production has high costs and large carbon emissions during the production process, which leads to increased costs or difficulty in advancing some projects.

[0004] Fluoropyrogypsum, an industrial solid waste, has a mineral composition similar to natural anhydrite, providing the necessary conditions for its potential use as a substitute. It can chemically react with other filler materials to produce a cementing effect, making it a green filler material. Producing it as a fluorogypsum-based cementitious material inherently enhances the environmental friendliness of some engineering projects. The carbon emissions during the production of fluorogypsum filler materials are far lower than those of cement-based filler materials, and the cost is also significantly reduced.

[0005] Currently, there are some cases of using fluorogypsum to prepare filling cementitious materials, but the fluorogypsum content is low, accounting for less than 50% of the total mass of the filling cementitious materials, which greatly limits the application of gypsum-based materials, especially in humid environments.

[0006] Fluorogypsum-based materials are mostly used in coating production, and their application environment is generally at normal temperature and humidity, making them unsuitable for large-scale use as cementing materials. CN104193285A discloses a high-performance modified fluorogypsum with a softening coefficient of 0.95 and a compressive strength of 19.6 MPa after 24 hours of curing. CN114890699A discloses a fluorogypsum-based cementing material and its preparation method, in which fluorogypsum is preheated, calcined, and then cooled to 60–100°C before mixing. The average strength after 28 days is 38.5 MPa, and the softening coefficient is between 0.65 and 0.85, but the process is complex. Both of the fluorogypsum cementing materials provided in these two patents exhibit some water resistance, but the curing environments used are not high-humidity environments, and their water resistance in high-humidity environments remains unclear. CN114853433A describes a fluorogypsum composite cementitious material and its preparation method. Although the average strength is above 45 MPa after 7 days of curing in a high humidity environment (20±2℃, relative humidity of 50~60%), the highest strength is only 10.5 MPa after 28 days, with a strength decrease of 76.7%.

[0007] Therefore, to overcome the above shortcomings, a fluorogypsum-based cementitious material with high water resistance was developed, so that its strength can continue to develop even in high humidity environments. Summary of the Invention

[0008] The purpose of this invention is to provide a highly water-resistant gypsum-based cementitious material that combines the advantages of good water resistance and high strength, in order to solve the problems of excessive accumulation, insufficient utilization, low strength, poor hydraulic properties, and limited applicable environment of fluorogypsum.

[0009] To achieve the above objectives, the present invention provides the following technical solution:

[0010] A highly water-resistant gypsum-based cementitious material comprises, by mass ratio, the following raw materials: 60%–70% fluorogypsum, 15%–25% fly ash, 9%–15% cement, 3%–6% slag powder, 0.04%–0.1% modified silica, and 0.1%–0.5% CSH seed crystals; it also includes a pH adjuster and an activator; wherein the pH adjuster accounts for 1%–5% of the total mass of fluorogypsum and fly ash, and the activator accounts for 0.5%–3% of the total mass of fluorogypsum and fly ash.

[0011] Preferably, the pH adjuster includes at least one of carbide slag and sodium hydroxide.

[0012] Preferably, the activator includes at least one of potassium sulfate, sodium sulfate, and alum.

[0013] Preferably, the modified silicon oxide surface has hydrophobic and hydrophilic groups.

[0014] Preferably, the modified silicon dioxide is prepared by the following method:

[0015] Prepare a 0.02–0.03 M sodium citrate solution with ammonia water, controlling its pH to 11.5–13. Add 0.5–1 parts by weight of PVP, 1–2 parts by weight of ethanol, and 0.5–1 parts by weight of sodium citrate-ammonia solution to 10–15 parts by weight of pentanol and mix thoroughly. Then add 0.1–1 parts by weight of tetraethyl orthosilicate, 0.005–0.15 parts by weight of chloropropyltrimethoxysilane, and 0.01–0.2 parts by weight of graphene oxide. Heat to 50–60 °C and stir at 600–800 r / min for 5–7 h. After centrifugation, washing, and drying, obtain the modified silica.

[0016] Preferably, the CSH seed crystals are prepared using the following method:

[0017] Calcium nitrate tetrahydrate and sodium silicate were added to a sodium hydroxide solution, and the pH was controlled at 12-13. The reaction was carried out for 1-2 hours, and CSH seed crystals were obtained after centrifugation and drying.

[0018] Preferably, the modified silicon dioxide is obtained by washing with ethanol or deionized water 2-3 times after centrifugation and drying at 50-60°C.

[0019] Preferably, the modified silicon dioxide is prepared by the following method:

[0020] Prepare a 0.022M sodium citrate solution with ammonia water, controlling its pH to 12.4. Add 1 part by weight of PVP, 1 part by weight of ethanol, and 0.6 parts by weight of sodium citrate-ammonia solution to 10 parts by weight of pentanol and mix thoroughly. Then add 0.1 part by weight of tetraethyl orthosilicate, 0.01 part by weight of chloropropyltrimethoxysilane, and 0.05 part by weight of graphene oxide. Heat to 50-60°C and stir at 700 r / min for 5 h. After centrifugation and drying, obtain the modified silica.

[0021] The preparation method of any one of the above-mentioned highly water-resistant gypsum-based cementitious materials includes the following steps:

[0022] S1. Weigh out fluorogypsum, fly ash, cement, and slag powder according to the proportions and mix them evenly to obtain a dry mixture;

[0023] S2. Weigh out the pH adjuster, activator, modified silica, and CSH seed crystals according to the proportion, add them together with the dry mixture to water and stir thoroughly to obtain the final product.

[0024] Preferably, in step S2, the water-to-glue ratio is 0.35 to 0.45.

[0025] Beneficial effects:

[0026] (1) This invention uses fluorogypsum as raw material, supplemented with fly ash, slag powder and a small amount of cement, and adds modified silica with hydrophilic and hydrophobic groups. The hydrophilic groups of the modified silica can ensure the normal hydration process, and the hydrophobic groups can prevent excessive water from penetrating the concrete, maintain the strength development of the concrete prepared by the fluorogypsum-based cementitious material, solve the problem of the fluorogypsum-based material being not water-resistant, and enable the fluorogypsum-based cementitious material to be used extensively in high humidity environments; in addition, the added CSH seed crystals can improve the early strength and are conducive to the formation of CSH.

[0027] (2) Fluorogypsum has a pH of around 4, which can create an acidic environment, which is not conducive to the hydration of the fluorogypsum cementing system. This invention introduces carbide slag, which on the one hand provides an alkaline environment to neutralize the acidity of fluorogypsum, and on the other hand realizes the reuse of carbide slag, an industrial waste. If sodium hydroxide is used for neutralization, because fluorogypsum is not water-resistant, sodium hydroxide is easily lost with the free water inside the cementing material when it is in a high humidity environment for a long time. The addition of carbide slag solves this problem well.

[0028] (3) This invention realizes the large-scale utilization of industrial solid wastes such as fluorogypsum, reduces the pollution of solid waste to the ecological environment, realizes the comprehensive utilization of fluorogypsum, and is conducive to the recycling of industrial resources and sustainable development. Attached Figure Description

[0029] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. Wherein:

[0030] Figure 1 The compressive strength trend diagrams of the test blocks provided in Examples 1-3 and Comparative Examples 1-3 of the present invention are shown. Detailed Implementation

[0031] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention are within the scope of protection of the present invention.

[0032] The present invention will now be described in detail with reference to embodiments. It should be noted that, unless otherwise specified, the embodiments and features described in the embodiments of the present invention can be combined with each other.

[0033] This invention addresses the problems of environmental pollution caused by the accumulation of industrial solid waste fluorogypsum and the high cost of backfill materials by providing a highly water-resistant gypsum-based cementitious material, comprising the following raw materials by mass ratio:

[0034] Fluorogypsum 60%–70% (e.g., 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%), fly ash 15%–25% (e.g., 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%), cement 9%–15% (e.g., 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%), slag powder 3%–6% (e.g., 3.5%, 4.0%, 4.5%, 5.0%, 5.5%), modified silica 0.04%–0.1% (e.g., 0.0%). The product contains 5%, 0.06%, 0.07%, 0.08%, and 0.09% of fluorogypsum and fly ash, and 0.1% to 0.5% of CSH seed crystals (e.g., 0.15%, 0.20%, 0.25%, 0.30%, 0.35%, 0.40%, and 0.45%). It also includes pH adjusters and activators; wherein the pH adjusters account for 1% to 5% of the total mass of fluorogypsum and fly ash (e.g., 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, and 4.5%), and the activators account for 0.5% to 3% of the total mass of fluorogypsum and fly ash (e.g., 0.6%, 0.8%, 1.0%, 1.5%, 2.0%, 2.5%, and 2.9%).

[0035] This invention incorporates modified silica with both hydrophilic and hydrophobic groups. The hydrophilic groups of the modified silica ensure proper hydration, while the hydrophobic groups prevent excessive water intrusion into the concrete, thus maintaining the strength development of concrete formulated with fluorogypsum-based cementitious materials. This solves the problem of fluorogypsum-based materials being intolerant to water, enabling the widespread use of fluorogypsum-based cementitious materials in high-humidity environments.

[0036] In a preferred embodiment of the present invention, the pH adjuster includes at least one of carbide slag and sodium hydroxide.

[0037] In a preferred embodiment of the present invention, the activator includes at least one of potassium sulfate, sodium sulfate, and alum.

[0038] In a preferred embodiment of the present invention, the modified silicon oxide surface has hydrophobic and hydrophilic groups.

[0039] In a preferred embodiment of the present invention, the modified silicon oxide is prepared as follows:

[0040] Prepare sodium citrate solution with a concentration of 0.02–0.03 M (e.g., 0.02 M, 0.025 M, 0.03 M) using ammonia water, controlling its pH to 11.5–13 (e.g., 11.6, 11.7, 11.8, 11.9). Add 0.5–1 (e.g., 0.6, 0.7, 0.8, 0.9) parts by weight of PVP and 1–2 (e.g., 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9) parts by weight of ethanol. Add 0.5–1 (e.g., 0.6, 0.7, 0.8, 0.9) parts by weight of sodium citrate-ammonia solution to 10–15 (e.g., 11, 12, 13, 14) parts by weight of pentanol and mix thoroughly; then add 0.1–1 (e.g., 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9) parts by weight of tetraethyl orthosilicate and 0.005–0.15 (e.g., 0.010, 0.02, 0.03, 0.05, 0.07, 0.09) parts by weight of pentanol. 0.09, 0.10, 0.12, 0.14) parts by weight of chloropropyltrimethoxysilane and 0.01–0.2 (e.g., 0.02, 0.03, 0.04, 0.05, 0.07, 0.09, 0.10, 0.15, 0.19) parts by weight of graphene oxide, heated to 50–60°C (e.g., 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C), at 600–800 r / min (e.g., 61 r / min). The mixture was stirred at 0 r / min, 630 r / min, 650 r / min, 670 r / min, 690 r / min, 700 r / min, 720 r / min, 740 r / min, 760 r / min, 780 r / min, and 790 r / min for 5 to 7 hours (e.g., 5.1 h, 5.5 h, 5.9 h, 6.0 h, 6.1 h, 6.5 h, and 6.9 h), centrifuged, washed, and dried to obtain the modified silica.

[0041] In a preferred embodiment of the present invention, the CSH seed crystals are prepared as follows:

[0042] Calcium nitrate tetrahydrate and sodium silicate are added to a sodium hydroxide solution, and the pH is controlled at 12-13 (e.g., 12.1, 12.2, 12.3, 12.4, 12.5, 12.6, 12.7, 12.8, 12.9). The reaction is carried out for 1-2 hours (e.g., 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9). After centrifugation and drying, CSH seed crystals are obtained.

[0043] In a preferred embodiment of the present invention, the modified silicon oxide is obtained by washing with ethanol or deionized water 2 to 3 times after centrifugation and drying at 50 to 60°C (e.g., 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C).

[0044] In a preferred embodiment of the present invention, the modified silicon oxide is prepared as follows:

[0045] Prepare a 0.022M sodium citrate solution with ammonia water, controlling its pH to 12.4. Add 1 part by weight of PVP, 1 part by weight of ethanol, and 0.6 parts by weight of sodium citrate-ammonia solution to 10 parts of pentanol and mix thoroughly. Then add 0.1 part by weight of tetraethyl orthosilicate, 0.01 part by weight of chloropropyltrimethoxysilane, and 0.05 part by weight of graphene oxide. Heat to 50-60°C (e.g., 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C), stir at 700 r / min for 5 h, and centrifuge and dry to obtain the modified silica.

[0046] The preparation method of any one of the above-mentioned highly water-resistant gypsum-based cementitious materials includes the following steps:

[0047] S1. Weigh out fluorogypsum, fly ash, cement, and slag powder according to the proportions and mix them evenly to obtain a dry mixture;

[0048] S2. Weigh out the pH adjuster, activator, modified silica, and CSH seed crystals according to the proportion, add them together with the dry mixture to water and stir thoroughly to obtain the final product.

[0049] In a preferred embodiment of the present invention, in step S2, the water-to-binder ratio is 0.35 to 0.45 (e.g., 0.36, 0.37, 0.38, 0.39, 0.30, 0.31, 0.32, 0.33, 0.34).

[0050] The following detailed description of a highly water-resistant gypsum-based cementitious material and its preparation method according to specific embodiments of the present invention is provided below.

[0051] The raw materials used in the following examples and comparative examples are from the following sources:

[0052] Cement, P·O42.5 grade ordinary Portland cement, purchased from Jiaozuo Qianye Cement Co., Ltd.;

[0053] Sodium hydroxide, analytical grade, purchased from Hongyan Reagent Factory, Hedong District, Tianjin.

[0054] Potassium sulfate, analytical grade, purchased from Tianjin Kemeo Chemical Reagent Co., Ltd.

[0055] Sodium sulfate, analytical grade, purchased from Tianjin Kemeo Chemical Reagent Co., Ltd.

[0056] PVP (polyvinylpyrrolidone), analytical grade, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0057] Calcium nitrate tetrahydrate, analytical grade, purchased from Tianjin Kemeo Chemical Reagent Co., Ltd.

[0058] Sodium silicate, analytical grade, purchased from Tianjin Kemeo Chemical Reagent Co., Ltd.

[0059] Tetraethyl orthosilicate, analytical grade, purchased from Tianjin Kemeo Chemical Reagent Co., Ltd.

[0060] Chloropropyltrimethoxysilane, analytical grade, purchased from Shanghai Maclean Biochemical Technology Co., Ltd.

[0061] Graphene oxide, powder, analytical grade, purchased from Shenzhen Suiheng Technology Co., Ltd.

[0062] Sodium citrate, analytical grade, purchased from Hongyan Reagent Factory, Hedong District, Tianjin.

[0063] Ethanol, analytical grade, purchased from Shanxi Tongjie Chemical Reagent Co., Ltd.

[0064] Ammonia solution, analytical grade, purchased from Luoyang Chemical Reagent Factory;

[0065] Pentanol, analytical grade, purchased from Shanghai Maclean Biochemical Technology Co., Ltd.

[0066] The CSH seed crystal preparation method used in the following examples is as follows:

[0067] Prepare a solution of calcium nitrate tetrahydrate (0.2 M–0.5 M), sodium silicate (0.2 M–0.5 M), and sodium hydroxide (10 M). Allow the calcium nitrate tetrahydrate to react with the sodium silicate. During the reaction, control the pH to 12–13 with sodium hydroxide solution. React for 1–2 hours, then centrifuge and dry to obtain CSH seed crystals.

[0068] In addition, commercially available CSH seed crystals can be used as a substitute.

[0069] The compositions of fluorogypsum, fly ash, carbide slag, and slag powder used in the following examples and comparative examples are as follows:

[0070] Table 1 Main Chemical Composition of Raw Materials

[0071]

[0072] Example 1

[0073] This embodiment provides a highly water-resistant fluorogypsum-based cementitious material, the raw materials of which, by weight, include: 69% fluorogypsum, 15% fly ash, 11% cement, 5% slag powder, 1.5% carbide slag, 0.5% sodium hydroxide, 1% potassium sulfate, 0.1% modified silica, and 0.3% CSH seed crystals.

[0074] The preparation method of modified silica is as follows:

[0075] Prepare a 0.022M sodium citrate solution with ammonia water, controlling its pH to 12.4. Add 1 part by weight of PVP, 1 part by weight of ethanol, and 0.6 parts by weight of sodium citrate-ammonia solution to 10 parts of pentanol and mix thoroughly. Then add 0.1 part by weight of tetraethyl orthosilicate, 0.01 part by weight of chloropropyltrimethoxysilane, and 0.05 part by weight of graphene oxide. Heat to 50-60℃, stir at 700 r / min for 5 h, and centrifuge and dry to obtain modified silica.

[0076] The preparation process of this highly water-resistant fluorogypsum-based cementitious material is as follows:

[0077] S1. Weigh out fluorogypsum, fly ash, cement, and slag powder according to the proportions and mix them evenly to obtain a dry mixture;

[0078] S2. Weigh out the pH adjuster, activator, modified silica, and CSH seed crystals according to the proportion. Add them together with the dry mixture in water at a water-to-binder ratio of 0.4 and stir thoroughly to obtain the final product.

[0079] Example 2

[0080] This embodiment provides a highly water-resistant fluorogypsum-based cementitious material, the raw materials of which, by weight, include: 69% fluorogypsum, 15% fly ash, 11% cement, 5% slag powder, 1.5% carbide slag, 0.5% sodium hydroxide, 1% potassium sulfate, 0.08% modified silica, and 0.3% CSH seed crystals.

[0081] The preparation method of this highly water-resistant fluorogypsum-based cementitious material is as described in Example 1.

[0082] Example 3

[0083] This embodiment provides a highly water-resistant fluorogypsum-based cementitious material, the raw materials of which, by weight, include: 63% fluorogypsum, 20% fly ash, 14% cement, 3% slag powder, 1.5% carbide slag, 0.5% sodium hydroxide, 1% potassium sulfate, 0.04% modified silica, and 0.5% CSH seed crystals.

[0084] The preparation method of this highly water-resistant fluorogypsum-based cementitious material is as described in Example 1.

[0085] Comparative Example 1

[0086] This embodiment provides a fluorogypsum-based cementitious material, the raw materials of which, by weight, include: 69% fluorogypsum, 15% fly ash, 11% cement, 5% slag powder, 1.5% carbide slag, 0.5% sodium hydroxide, 1% potassium sulfate, and 0.3% CSH seed crystals.

[0087] The preparation method of this fluorogypsum-based cementitious material is as described in Example 1.

[0088] Comparative Example 2

[0089] This embodiment provides a fluorogypsum-based cementitious material, the raw materials of which, by weight, include: 69% fluorogypsum, 15% fly ash, 11% cement, 5% slag powder, 1.5% carbide slag, 0.5% sodium hydroxide, and 1% potassium sulfate.

[0090] The preparation method of this fluorogypsum-based cementitious material is the same as that of Comparative Example 1.

[0091] Comparative Example 3

[0092] This embodiment provides a fluorogypsum-based cementitious material, the raw materials of which, by weight, include: 69% fluorogypsum, 15% fly ash, 11% cement, 5% slag powder, 1.5% carbide slag, 0.5% sodium hydroxide, and 1% sodium sulfate.

[0093] The preparation method of this fluorogypsum-based cementitious material is the same as that of Comparative Example 1.

[0094] Performance testing:

[0095] The gelling materials prepared in Examples 1-3 and Comparative Examples 1-3 were stirred evenly and then poured into a triple mold with dimensions of 40mm×40mm×40mm to form the gelling material. After sealing, the mold was placed in a curing room and cured for 24 hours under high humidity conditions of 20±2℃ and relative humidity ≥95%. The mold was then removed, and the curing continued until 7 days and 28 days of age. Finally, the compressive strength of the specimens was tested using a pressure machine, as shown in Table 2 below.

[0096] Table 2 shows the compressive strength of the specimens obtained in Examples 1-3 and Comparative Examples 1-3.

[0097]

[0098]

[0099] like Figure 1 As shown in Table 2 above, when cured in a high humidity environment with a relative humidity of ≥95%, the 28-day compressive strength of Examples 1-3 was significantly higher than that of Comparative Examples 2 and 3. This indicates that the addition of modified silica and CSH seed crystals can significantly improve the water resistance of the cementitious material, thereby increasing its compressive strength in a high humidity environment. Meanwhile, the compressive strength of the test blocks in Examples 1-3 showed a continuous increasing trend with the increase of curing age, while the test blocks in Comparative Examples 1-3, although having higher compressive strength at 1 day and 7 days, showed a significant decrease in compressive strength at 28 days of curing, exhibiting a trend of "rapid increase followed by significant decrease". This indicates that their water resistance is poor and it is difficult to maintain high strength for a long time in a high humidity environment, which is extremely detrimental to the service life and safety of the cementitious material during service.

[0100] Secondly, from Figure 1As can be seen from the data in Table 2, although the addition of modified silica with hydrophobic groups had a certain negative effect on the early strength of the cementitious material, the strength of the cementitious materials provided in Examples 1 to 3 could still maintain a rapid growth trend throughout the curing period due to the presence of hydrophilic groups, and was only slightly lower than that of the cementitious material without modified silica.

[0101] Data from Examples 1-3 and Comparative Example 1 show that adding an appropriate amount of CSH seed crystals helps to improve the early strength of cementitious materials. However, the amount of CSH seed crystals added is not necessarily better the more it is added, but rather it is influenced by the amount of modified silica added.

[0102] In summary:

[0103] This invention provides a highly water-resistant gypsum-based cementitious material. Its water resistance is improved by adding modified silica with hydrophobic groups. The modified silica has undergone dual modification of hydrophobicity and hydrophilicity. Its hydrophilic groups can offset part of the influence of hydrophobic groups on the hydration of the cementitious material. CSH seed crystals are also added to further reduce the influence of the hydrophobicity of the modified silica on the early strength. At the same time, it shows a positive effect on the water resistance of the material.

[0104] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A highly water-resistant gypsum-based cementitious material, characterized in that, By mass ratio, it includes the following raw materials: 60%–70% fluorogypsum, 15%–25% fly ash, 9%–15% cement, 3%–6% slag powder, 0.04%–0.1% modified silica, and 0.1%–0.5% CSH seed crystals. It also includes pH adjuster and activator; wherein the pH adjuster accounts for 1%–5% of the total mass of fluorogypsum and fly ash, and the activator accounts for 0.5%–3% of the total mass of fluorogypsum and fly ash. The modified silica has hydrophobic and hydrophilic groups on its surface, and its preparation method is as follows: Sodium citrate with a concentration of 0.02–0.03 M is prepared using ammonia water, and its pH is controlled at 11.5–13. 0.5–1 parts by weight of PVP, 1–2 parts by weight of ethanol, and 0.5–1 parts by weight of sodium citrate-ammonia solution are added to 10–15 parts by weight of pentanol and mixed thoroughly. Then, 0.1–1 parts by weight of tetraethyl orthosilicate, 0.005–0.15 parts by weight of chloropropyltrimethoxysilane, and 0.01–0.2 parts by weight of graphene oxide are added. The mixture is heated to 50–60°C and stirred at 600–800 r / min for 5–7 h. After centrifugation, washing, and drying, the modified silica is obtained. The CSH seed crystals are prepared as follows: calcium nitrate tetrahydrate and sodium silicate are added to sodium hydroxide solution, the pH is controlled at 12-13, the reaction is carried out for 1-2 hours, and the CSH seed crystals are obtained after centrifugation and drying.

2. The highly water-resistant gypsum-based cementitious material as described in claim 1, characterized in that, The pH adjuster includes at least one of carbide slag and sodium hydroxide.

3. The highly water-resistant gypsum-based cementitious material as described in claim 1, characterized in that, The activator includes at least one of potassium sulfate, sodium sulfate, and alum.

4. The highly water-resistant gypsum-based cementitious material as described in claim 1, characterized in that, After centrifugation, wash 2-3 times with ethanol or deionized water, and dry at 50-60°C to obtain the modified silicon dioxide.

5. The highly water-resistant gypsum-based cementitious material as described in claim 1, characterized in that, The modified silica is prepared as follows: Sodium citrate with ammonia water is prepared to a concentration of 0.022M, and its pH is controlled at 12.

4. 1 part by weight of PVP, 1 part by weight of ethanol, and 0.6 parts by weight of sodium citrate-ammonia solution are added to 10 parts by weight of pentanol and mixed thoroughly. Then, 0.1 part by weight of tetraethyl orthosilicate, 0.01 part by weight of chloropropyltrimethoxysilane, and 0.05 part by weight of graphene oxide are added. The mixture is heated to 50–60°C, stirred at 700 r / min for 5 h, and then centrifuged and dried to obtain the modified silica.

6. A method for preparing a highly water-resistant gypsum-based cementitious material as described in any one of claims 1 to 5, characterized in that, Includes the following steps: S1. Weigh out fluorogypsum, fly ash, cement, and slag powder according to the proportions and mix them evenly to obtain a dry mixture; S2. Weigh out the pH adjuster, activator, modified silica, and CSH seed crystals according to the proportion, add them together with the dry mixture to water and stir thoroughly to obtain the final product.

7. The method for preparing a highly water-resistant gypsum-based cementitious material as described in claim 6, characterized in that, In step S2, the water-to-glue ratio is 0.35 to 0.45.

Citation Information

Patent Citations

  • High-performance modified fluorogypsum

    CN104193285A

  • Gelling material prepared from fluorgypsum and preparation method of cementing material

    CN114890699A

  • Fluorine gypsum composite cementing material and preparation method thereof

    CN114853433A

  • Titanium gypsum mineral powder-based composite cementing material

    CN114920475A

  • Super early strength concrete and preparation method thereof

    CN116041004A